Study of Perceptions on Clean and Self-Sustainable Energy (2018)
The objective of this article, is to identify the perceived benefits from the implementation of solar panels to generate clean, economical and sustainable energy at the Arcesio Caliz Amador School. Initially, the community supported the promotion of alternative energy sources and assessed different types of natural and artificial energy sources. A prototype solar panel was developed and awareness-raising efforts were made in the community to promote the use of alternative energy sources and caring for the environment. This study is quantitative and experimental. The study uses the technique of structured interviews with a sample of 50 students from the Arcesio Caliz Amador School. The main finding is that the students recognize that the use and implementation of this type of energy offers environmental, educational, economic and social benefits.